Gut microbiota causally affects drug-induced liver injury via plasma metabolites: a Mendelian randomization study - Fu, Haoshuang; Zhao, Shuang; Song, Shuying; Xie, Qing (Frontiers in Microbiology, 2024)
Background The gut microbiota and plasma metabolites play important roles in the progression of drug-induced liver injury (DILI). We investigated the causal associations between the gut microbiota, plasma metabolome, and DILI. Methods The summary data for gut microbiota (n = 18,340), plasma metabolome (n = 8,299), and DILI (n = 366,838) were obtained from the large genome-wide association studies. A two-sample Mendelian randomization was performed to explore the associations between the gut microbiota, plasma metabolome, and DILI. Additionally, a two-step Mendelian randomization was performed to explore the potential metabolites. Results Five taxa were causally associated with DILI, including Oscillospira [odds ratio (OR) = 2.257, 95% confidence interval (CI) = 1.110–4.590], Blautia (OR = 2.311, 95% CI = 1.010–5.288), Roseburia (OR = 2.869, 95% CI = 1.429–5.761), Fusicatenibacter (OR = 1.995, 95% CI = 1.024–3.890), and Prevotella 7 (OR = 1.549, 95% CI = 1.065–2.253). Moreover, 53 metabolites were causally associated with DILI. After mediation analysis, four taxa were found to affect DILI through five mediation metabolites. N6-carbamoylthreonyladenosine mediated the effect of Blautia on DILI. Acetylcarnitine mediated the effect of Fusicatenibacter on DILI. In addition, 4-cholesten-3-one mediated the effect of Prevotella 7 on DILI. Furthermore, 5,6-dihydrothymine levels and the salicylate-to-citrate ratio mediated the effect of Oscillospira on DILI. Conclusion We found that the gut microbiota could affect DILI through plasma metabolites, which could serve as potential biomarkers for risk stratification and elucidate underlying mechanisms for further investigation of DILI.